CFD based mini- vs. micro-system delineation in elongated bubble flow regime - Rek, Zlatko; Zun, Iztok (International journal of multiphase flow, 2014)
•The delineation criteria between mini- and micro-systems is proposed.•3D VOF numerical simulation was successfully validated with experimental data.•Channels with D⩽100μm can be characterized as a micro-system.•Channels with D⩾400μm can be characterized as a mini-system.•Region 200μm⩽D⩽300μm represents a transition between micro- to mini-scale. Delineation of mini- and micro-scale channels with respect to two-phase flow has been the subject of many research papers. There is no consensus on when the small channel can be characterized as a mini-channel or micro-channel. The idea proposed by this paper is to use the normalized bubble nose radius, liquid film thickness top over bottom ratio, and bubble shape contour, which are found under normal gravity conditions in slug flow through a horizontal adiabatic channel, as the delineation criteria. The input parameters are bubble nose radius and bubble nose velocity as the characteristic length scale and characteristic velocity scale respectively. 3D numerical simulation with ANSYS FLUENT was used to obtain the necessary data. Following CFD practice, a mesh independence study and a numerical model validation against published experimental data were both conducted. Analysis of the numerical simulation results showed that channels with D⩽100μm can be characterized as a micro-system, while channels with D⩾400μm belong to mini-systems. The region 200μm⩽D⩽300μm represents a transition from the micro-scale to mini-scale.